2013
DOI: 10.1186/1471-2458-13-382
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and practices related to visceral leishmaniasis among residents in Addis Zemen town, South Gondar, Northwest Ethiopia

Abstract: BackgroundVisceral leishmaniasis (VL), commonly known as kala-azar is a systemic disease caused by parasitic protozoan species of genus Leishmania and transmitted by species of Phlebotomus (sand flies). It is a poverty-related disease and associated with malnutrition, displacement, poor housing, weakness of the immune system and lack of resources. For the success of prevention and control programs of any disease, the most important prerequisite is community participation. Therefore, this study was aimed to ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
54
22
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(95 citation statements)
references
References 17 publications
18
54
22
1
Order By: Relevance
“…And compared to attitude, knowledge had a higher correlation with the participants' practice. The findings of the present study indicated that the knowledge of the participants in the study was below average and this was consistent with the findings of previous studies [13,14] but it was not consistent with the study by Alemu [15]. Low awareness of the people about leishmaniasis is a serious alarm due to the rising trend of the disease in recent years and also, the serious and close attention of the Ministry of Health and universities of Medical Sciences on leishmaniasis is requured.…”
Section: Resultssupporting
confidence: 59%
“…And compared to attitude, knowledge had a higher correlation with the participants' practice. The findings of the present study indicated that the knowledge of the participants in the study was below average and this was consistent with the findings of previous studies [13,14] but it was not consistent with the study by Alemu [15]. Low awareness of the people about leishmaniasis is a serious alarm due to the rising trend of the disease in recent years and also, the serious and close attention of the Ministry of Health and universities of Medical Sciences on leishmaniasis is requured.…”
Section: Resultssupporting
confidence: 59%
“…The identified KA HH had a total population of 451 with 243 male and 208 females, 53.8% male and 46.1% females, Sharma BP et 13 al . In contrast to another study of Bihar where majority 14 (97.0%) of the respondents were males in the current study majority (50.5%) of the respondents were female, however it is supported by the study conducted in South Gondar where 15 majority of the respondents were female 60.7% .…”
Section: Discussioncontrasting
confidence: 99%
“…Also in the urban area of Libo Kemkem knowledge regarding causes was higher and more specific, as 68% of interviewee reported sandflies as the VL causal agent [19].…”
Section: Discussionmentioning
confidence: 97%